Communicating with Allah - Omer, Spahic (IslamiCity, 2019)
Almighty Allah as the Creator communicates with His creation. He does so in various ways most of which are unknown to man. He informs us through His revealed Word, the Holy Qur’an, for example, that He communicates with the heavens, the earth, mountains, the fire, hellfire, animals, etc.